Mutational Analysis of TYR, OCA2, and SLC45A2 Genes in Chinese Families with Oculocutaneous Albinism. Issue 7 (14th June 2019) - Lin, Ye; Chen, Xihui; Yang, Ying; Che, Fengyu; Zhang, Sijia; Yuan, Lijuan; Wu, Yuanming
Abstract: Background: Oculocutaneous albinism (OCA) is a group of heterogeneous autosomal recessive genetic disorder of melanin synthesis results in hypopigmented hair, skin, and eyes. OCA type 1, OCA type 2, and OCA type 4, which are respectively caused by mutations in TYR, OCA2, and SLC45A2 have high morbidity rates in Asia. Methods: TYR, OCA2, and SLC45A2 mutation analysis was carried out on 18 nonconsanguineous OCA patients and four fetuses were included for prenatal diagnose. Three genes of all individuals were amplified by polymerase chain reaction and examined by Sanger sequencing. The pathogenicity of the detected mutations were analyzed by Mutation Taster, PolyPhen 2, and SIFT software, and the conservation of the substituted amino acids were analyzed by MEGA software. Results: Eleven TYR mutations, three OCA2 mutations, and two SLC45A2 mutations were identified in 14 OCA type 1 patients, two OCA type 2 patients, and two OCA type 4 patients. c.1021A>G, p.R341G in TYR, c.1096_1104del, p.V366*, and c.1079C>T, p.S360F in OCA2 were novel. One of the four fetuses carried compound heterozygous mutation of TYR and became spontaneous abortion, the other three carried no mutations and appeared normal at birth. Conclusion: In this study, specific clinical characteristics of OCA patients were described. Three novel pathogenic mutations were identified which will enrich the mutation spectrum of OCA, and the prenatal genetic screening in fetus at risk of OCA can provide vital information for genetic counseling. Abstract : By using the sequencing technology, 16 mutations located in three genes (TYR, OCA2, and SLC45A2) were identified. In this paper, comprehensive clinical characteristics of the 18 OCA patients are recorded, which will give more evidence for the diagnosis of the disease. Three novel mutations have never been reported before were identified, which will enrich the worldwide spectrum of OCA. Moreover, three families accepted prenatal genetic screening for fetus at risk of OCA, which provided vital information for genetic counseling of couples at risk.